BBIT20 inhibits homologous DNA repair with disruption of the BRCA1–BARD1 interaction in breast and ovarian cancer. (11th June 2021) - Raimundo, Liliana; Paterna, Angela; Calheiros, Juliana; Ribeiro, Joana; Cardoso, David S. P.; Piga, Ilaria; Neto, Susana Junqueira; Hegan, Denise; Glazer, Peter M.; Indraccolo, Stefano; Mulhovo, Silva; Costa, José Luís; et al.
Abstract : Background and Purpose: Advances in the treatment of triple‐negative breast and ovarian cancer remain challenging. In particular, resistance to the available therapy, by restoring or overexpressing the DNA repair machinery, has often been reported. New strategies to improve the therapeutic outcomes of these cancers are needed. Herein, we disclose the dregamine 5‐bromo‐pyridin‐2‐ylhydrazone (BBIT20), a natural monoterpene indole alkaloid derivative, as an inhibitor of homologous DNA repair. Experimental Approach: To unveil BBIT20 antitumour activity and underlying molecular mechanism of action, two‐dimensional (2D) and three‐dimensional (3D) cell cultures, patient‐derived cell lines and xenograft mouse models were used. Key Results: BBIT20 disrupted the BRCA1‐BARD1 interaction, triggering nuclear‐to‐cytoplasmic BRCA1 translocation, cell cycle arrest and downregulation of homologous DNA repair‐related genes and proteins, with subsequent enhancement of DNA damage, reactive oxygen species generation and apoptosis, in triple‐negative breast and ovarian cancer cells. BBIT20 also displayed pronounced antitumour activity in patient‐derived cells and xenograft mouse models of ovarian cancer, with low toxicity in non‐malignant cells and undetectable side effects in mice. Additionally, it did not induce resistance in triple‐negative breast and ovarian cancer and displayed marked synergistic effects with cisplatin and olaparib (a poly [ADP‐ribose] polymerase inhibitor), on 2D and 3D models of these cancer cells. Conclusion and Implications: These findings add an inhibitor of the BRCA1‐BARD1 interaction to the list of DNA‐damaging agents. Importantly, either as a single agent or in combination therapy, BBIT20 reveals great potential in the personalized treatment of aggressive and resistant cancers, particularly triple‐negative breast and advanced ovarian cancer.